Soil Organic Matter Status Vis-a-Vis Vegetation Cover in Langate Forests of Kashmir Himalaya - Lone, Helal A.; Rather, G. H. (Indian Forester, 2019)
Soil organic matter is generally used to represent any material produced originally by living organisms that is returned to the soil and goes through the decomposition process. Organic matter of forest soils is chiefly derived from plant litter. Deforestation of natural forests has induced a significant depletion in the stock of soil organic matter. In the present study, organic matter content of soils under different canopy covers was analyzed in Langate Forests in Kashmir Himalaya. In the present study, the organic matter content of the soils under tree was found higher than the under shrub and herb as statistically significant variations (P<0.001) were observed for an organic matter of these soils at all the sites. Further, the density of the canopy layer also seemed to influence the organic matter content of the soils as higher density sites revealed higher values than lower density sites.